Lipidic liquid crystalline cubic phases for preparation of ATP-hydrolysing enzyme electrodes - Zatloukalová, Martina; Nazaruk, Ewa; Novák, David; Vacek, Jan; Bilewicz, Renata (Biosensors & bioelectronics, 2018)
The lipidic liquid-crystalline cubic phase (LCP) is a membrane-mimetic material useful for the stabilization and structural analysis of membrane proteins. Here, we focused on the incorporation of the membrane ATP-hydrolysing sodium/potassium transporter Na+/K+-ATPase (NKA) into a monoolein-derived LCP. Small-angle X-ray scattering was employed for the determination of the LCP structure, which was of Pn3m symmetry for all the formulations studied. The fully characterized NKA-LCP material was immobilized onto a glassy carbon electrode, forming a highly stable enzyme electrode and a novel sensing platform. A typical NKA voltammetric signature was monitored via the anodic reaction of tyrosine and tryptophan residues. The in situ enzyme activity evaluation was based on the ability of NKA to transform ATP to ADP and free phosphate, the latter reacting with ammonium molybdate to form the ammonium phosphomolybdate complex under acidic conditions. The square-wave voltammetric detection of phosphomolybdate was performed and complemented with spectrophotometric measurement at 710nm. The anodic voltammetric response, corresponding to the catalytic ATP-hydrolysing function of NKA incorporated into the LCP, was monitored at around + 0.2V vs. Ag/AgCl in the presence or absence of ouabain, a specific NKA inhibitor. NKA incorporated into the LCP retained its ATP-hydrolysing activity for 7 days, while the solubilized protein became practically inactive. The novelty of this work is the first incorporation of NKA into a lipidic cubic phase with consequent enzyme functionality and stability evaluation using voltammetric detection. The application of LCPs could also be important in the further development of new membrane protein electrochemical sensors and enzyme electrodes.
Keywords: Models, Molecular; Enzyme Assays; Glycerides; enzymy imobilizované; Biosensing Techniques; Liquid Crystals; Enzymes, Immobilized; molekulární modely; enzymatické testy; adenosintrifosfát; prasata; Hydrolysis; biosenzitivní techniky; hydrolýza; Sodium-Potassium-Exchanging ATPase; sodíko-draslíková ATPasa; kapalné krystaly; Animals; glyceridy; zvířata; Adenosine Triphosphate; Swine